The NADPH Oxidases Nox1 and Nox2 Differentially Regulate Volatile Organic Compounds, Fungistatic Activity, Plant Growth Promotion and Nutrient Assimilation in Trichoderma atroviride - Cruz-Magalhães, Valter; Nieto-Jacobo, Maria Fernanda; van Zijll de Jong, Eline; Rostás, Michael; Padilla-Arizmendi, Fabiola; Kandula, Diwakar; Kandula, Janaki; Hampton, John; Herrera-Estrella, Alfredo; Steyaert, Johanna M.; Stewart, Alison; Loguercio, Leandro Lopes; et al. (Frontiers in Microbiology, 2019)
In eukaryotic systems, membrane-bound NADPH oxidases (Nox) generate reactive oxygen species (ROS) as a part of normal physiological functions. In the soil-borne mycoparasitic and plant facultative symbiont Trichoderma atroviride, Nox1 and the regulator NoxR are involved in differentiation induced by mechanical damage, while the role of Nox2 has not been determined. The knock-out strains ∆nox1, ∆noxR and ∆nox2 were compared to the parental strain (WT) in their ability to grow and conidiate under a series of stress conditions (osmotic, oxidative, membrane and cell-wall stresses). All three genes were differentially involved in the stress-response phenotypes. In addition, several interactive experiments with biotic factors (plant seedlings and other fungi) were performed comparing the mutant phenotypes with the WT, which was used as the reference strain. ∆nox1 and ∆noxR significantly reduced the antagonistic activity of T. atroviride against Rhizoctonia solani and Sclerotinia sclerotiorum in direct confrontation assays, but Δnox2 showed similar activity to the WT. The ∆nox1, ∆noxR and ∆nox2 mutants showed quantitative differences in the emission of several volatile organic compounds (VOCs). The effects of a blend of these volatiles on plant-growth promotion of Arabidopsis thaliana seedlings were determined in closed-chamber experiments. The increase in root and shoot biomass induced by T. atroviride VOCs was significantly lowered by ∆noxR and ∆nox1, but not by ∆nox2. In terms of fungistatic activity at a distance, ∆nox2 had a significant reduction in this trait against R. solani and S. sclerotiorum, while fungistasis was highly increased by ∆noxR and ∆nox1. Identification and quantification of individual VOCs in the blends emitted by the strains was performed by GC-MS and the patterns of variation observed for individual volatiles, such as 6-Pentyl-2H-pyran-2-one (6PP-1) and (E)-6-Pent-1-enylpyran-2-one (6PP-2) were consistent with their negative effects in plant-growth promotion and positive effects in fungistasis at a distance. Nox1 and NoxR appear to have a ubiquitous regulatory role of in a variety of developmental and interactive processes in T. atroviride either as positive or negative modulators. Nox2 may also have a role in regulating production of VOCs with fungistatic activity.